FINANCIAL LITERACY ANALYSIS MANAGEMENT ON FINANCIAL MANAGEMENT BEHAVIOR OF SATYAGAMA UNIVERSITY STUDENTS - Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Didi Sukardi; Murdiyono Murdiyono (Nusantara Hasana Journal, 2022)
Financial literacy is a crucial factor in shaping students' financial management behavior in the digital era. Students, as the younger generation, are expected to be able to manage their income, expenses, savings, and use digital financial services wisely. This study aims to analyze the influence of financial literacy on the financial management behavior of Satyagama University students. The research method used a descriptive quantitative approach with data collection through questionnaires from active Satyagama University students. Analysis was conducted using simple linear regression to determine the relationship between financial literacy variables and financial management behavior. The results showed that financial literacy has a positive and significant effect on students' financial management behavior. Students with a better level of financial understanding tend to be able to budget, control expenses, save, and avoid consumptive behavior. Therefore, improving financial literacy education in higher education environments needs to be carried out continuously so that students have good financial management skills in their daily lives.